2013
DOI: 10.5897/ajmr12.2361
|View full text |Cite
|
Sign up to set email alerts
|

Identification of extended-spectrum-beta-lactamases(ESBLs), metallo-beta-lactamases (MBLs), Amp-C and KPC -lactamases among Klebsiella pneumoniae isolated from adults and pediatric patients in Iran

Abstract: Klebsiella pneumoniae is one of the major bacteria that cause acute infections. β-lactamases are main defensive mechanisms in bacteria against drugs. The aim of this study was to determine antibiotic resistance patterns and detection of extended-spectrum-beta-lactamase (ESBL), MBL, Amp-C and KPC β-lactamases among K. pneumoniae strains isolated from adults and infants. This descriptive study was done on 83 K. pneumoniae isolated from two hospitals. Antibiotic susceptibility tests were performed by Kirby-Bauer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Decreased permeability of the outer membrane and increased efflux pump are the other mechanisms of carbapenem resistance [8, 9]. There are a number of MBLs genes such as imipenemase (IMP), Verona integron-encoded metallo-beta-lactamases (VIM), Sno Paolo metallo (SPM), New-Delhi metallo-β-lactamase (NDM), German imipenemase (GIM), Kyorin University Hospital imipenemase (KHM), and Australian imipenemase (AIM) [10, 11]. IMP, VIM and SPM are the most important genes of MBLs that have been detected in A .…”
Section: Introductionmentioning
confidence: 99%
“…Decreased permeability of the outer membrane and increased efflux pump are the other mechanisms of carbapenem resistance [8, 9]. There are a number of MBLs genes such as imipenemase (IMP), Verona integron-encoded metallo-beta-lactamases (VIM), Sno Paolo metallo (SPM), New-Delhi metallo-β-lactamase (NDM), German imipenemase (GIM), Kyorin University Hospital imipenemase (KHM), and Australian imipenemase (AIM) [10, 11]. IMP, VIM and SPM are the most important genes of MBLs that have been detected in A .…”
Section: Introductionmentioning
confidence: 99%
“…Different antibiotics such as aminoglycosides and betalactamases are commonly used to treat the infection caused by K. pneumoniae while the prevalence of antibiotic resistance has rapidly increased in recent years threatening global public health, especially in developing countries. 12,13 In fact, treating drug-resistant infections has become more challenging owing to the evolution of several antibiotic-resistance mechanisms resulted from widespread use and misuse of antibiotics. 12,13 In addition, based on the results of the present study, the isolates were mainly found to be susceptible to ertapenem, imipenem, meropenem, gentamicin, and amikacin.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In fact, treating drug-resistant infections has become more challenging owing to the evolution of several antibiotic-resistance mechanisms resulted from widespread use and misuse of antibiotics. 12,13 In addition, based on the results of the present study, the isolates were mainly found to be susceptible to ertapenem, imipenem, meropenem, gentamicin, and amikacin. Overall, 3 isolates were imipenem-resistant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation